Pengembangan Lembaga SLB YPPC Banda Aceh dalam Meningkatkan Daya Saing di Era Modernisasi - Azhar Azhar (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
Development as an effort to improve one's technical, theoretical, conceptual and moral abilities in accordance with needs, is associated with the school of course through education and the need to achieve educational goals. In the world of education, school principals together with stakeholders strive to increase competitiveness. The purpose of this research is to describe the concept of developing SLB YPPC Banda Aceh in increasing competitiveness in the modernization era. This study uses a descriptive qualitative approach, namely a narrative description of the subject's behavior process in accordance with the focus of the problem under study. Data collection techniques using the method of observation, interviews and documentation. The results of the study show that YPPC Banda Aceh SLB, in developing schools to increase competitiveness is in accordance with the concept of the vision, mission and goals of the school. The quality of learning is in accordance with the national curriculum. In developing SLB YPPC Banda Aceh human resources in collaboration with parents of students, official agencies and other agencies. Facilities and infrastructure in support of human resource development activities and the development of learning activities that are real are adequately adapted to the times and technology, and SLB YPPC Banda Aceh maintains good relations with the local community and always involves the community in school activities.